Let?s Change University into a Better Factory - Zarębski, Tomasz (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The article is a polemics with the Oskar Szwabowski?s book Uniwersytet ? fabryka ? maszyna. Uniwersytet w perspektywie radykalnej (University ? factory ? machine. University in a radical perspective) (2014). Szwabowski diagnoses the present condition of university ? in Poland and in most Western countries ? as an institution fully subordinated to the hidden logic of Capital. Making use of Marxist analytical categories he presents a vision of Academy as a factory, where work loses its autonomy and becomes completely alienated, both in the educational and research sphere. What is interesting, Szwabowski is not trying to defend university against becoming a factory for the benefit of ?worker?s? perspective, as a rule escaping from the aristocratic perspective, which would give the university a special status of making it privileged. Moreover, in making university factory-like he sees a chance for a total and revolutionary change of the sorrounding neoliberal reality. The new proletariat that is affected by the yoke of exploitation, but at the same time able to discover and reveal the veiled mechanisms of Capital are nowadays the academics. According to Szwabowski, it is them who are the driving force of the future and looked-for revolution. The polemics with the above argumentation of Szwabowski indicates mainly the weakness of the empirical justification of the set theses and also a wishful character of the project of the social revolution, which is to be initiated by the academics.